2009
DOI: 10.1016/j.jtcvs.2008.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive video-assisted mitral valve surgery: A 12-year, 2-center experience in 1178 patients

Abstract: Video-assisted mitral valve surgery is safe with high rates of repair, low morbidity, and excellent outcomes. Reoperation after previous median sternotomy is not an independent predictor of mortality with this approach. Operative risk is increased if surgery is delayed until the onset of atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
89
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 34 publications
10
89
0
2
Order By: Relevance
“…Only one patient from G1 progressed to permanent sequel. Modi et al [51] also reported a 2.6% of CVA in 12 years of use of minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Only one patient from G1 progressed to permanent sequel. Modi et al [51] also reported a 2.6% of CVA in 12 years of use of minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Modi et al [40] showed 82% of mitral valve in their series and also mentioned in their reports these better results in the experience of other authors.…”
Section: Discussionmentioning
confidence: 62%
“…Twelve patients had postoperative complications, among them, three cases of stroke (3/105 or 2.9%), all patients with severe aortic valve calcification and only one developed sequelae. Modi et al [40] also reported a 2.6% of stroke in 12 years of use of the method.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations